Impact of dapagliflozin on metabolic phenotype, hormone levels, and fertility in female mice after prolonged high-fat diet - Chen, Xiaolin; Xiao, Zhuoni; Dai, Na; Fan, Mingxia (Frontiers in Endocrinology, 2025)
IntroductionA long-term high-fat diet (HFD) cause obesity and infertility through hypothalamic inflammation and insulin resistance, leading to metabolic abnormalities and ovulation dysfunction. The sodium-glucose cotransporter 2 inhibitors (SGLT2i) have emerged as a treatment for type 2 diabetic patients, regulating adipose tissue metabolism, hypothalamic inflammation, and ovulation in women with polycystic ovary syndrome (PCOS). The study aimed to investigate the pharmacological effects of dapagliflozin on improving insulin resistance, energy metabolism, sex hormones, and fertility in female mice following prolonged consumption of HFD.MethodsAt 6 weeks of age, female mice were fed a HFD and treated with dapagliflozin. Serum hormone concentrations and inflammatory factors in mice aged 28 weeks or 38 weeks were quantified using ultrasensitive enzyme-linked immunosorbent assays (ELISAs). Metabolic parameters were also assessed and documented at different stages of the experiment. At 34 weeks of age, half of the experimental mice in each of the four groups fed with standard chow were mated with male mice. Pregnancy rate, abortion rate, pregnancy-related deaths, and perinatal outcomes were systematically recorded.ResultsAfter 16 weeks of HFD feeding, dapagliflozin significantly attenuated visceral fat deposition, weight gain, glucose intolerance, and insulin resistance induced by the diet. However, these effects diminished after 32 weeks. Unexpectedly, neither HFD nor dapagliflozin treatment elicited any significant changes in serum IL-6 and TNFα levels. Throughout the experiment period, dapagliflozin exhibited favorable effects on reproductive function along with insulin sensitivity and luteinizing hormone (LH) release from the pituitary gland.DiscussionIn conclusion, this study demonstrates that dapagliflozin alleviated HFD-induced reproductive dysfunction independently of obesity, peripheral tissue insulin resistance, and systemic inflammation, suggesting its potential as a promising treatment for diet-related ovulation disorders.